A Method for Determination of Strength of Coal Mass - Qixiang Y (The Australasian Institute of Mining and Metallurgy, 1992)
The strength of coal mass saturated with gas is an essential parameter in studying the mechanism of gas and coal outburst,and its prediction method. Up to now, there has not been a method for determining the strength of coal mass saturated with gas.This paper describes a new method whereby the strength of in-situ coal mass can be determined and stored continuously and automatically. The simulation results obtained in the laboratory indicate that the new method allows a fast, reliable, inexpensive and convenient determination of the strength of coal mass.